2019
DOI: 10.32098/mltj.04.2019.09
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Dimensions of Achilles Tendon Insertional Area Using Ultrasound Imaging A Validity and Reliability Study

Abstract: Background. The purpose of this study was to evaluate the reliability and validity of using US imaging for measuring Achilles tendon insertion area to the calcaneus. Methods. Sixteen cadaveric tendons were used to compare the agreement between Achilles tendon insertion length measurements from US images with actual measurements after dissection. In addition, test-retest reliability was performed on six healthy subjects for tendon insertion length (IL), before calcaneal bone cross-sectional area (CSA) and tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
10
2
Order By: Relevance
“…In practice, the measurement concerned the length of the enthesis organ, and not only the tendon-bone connection. The insertion length reveled in our study is slightly longer than previously reported by ultrasound or research performed on the cadavers 40 . The differences in methods and population differences may explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In practice, the measurement concerned the length of the enthesis organ, and not only the tendon-bone connection. The insertion length reveled in our study is slightly longer than previously reported by ultrasound or research performed on the cadavers 40 . The differences in methods and population differences may explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 64%
“…The attachment measurement included the direct connection of the tendon with the bone and the area of the fibrocartilage layer on the calcaneus. Ultrasound could help distinguish between the part of the calcaneus covered by fibrocartilage and the connection between the tendon and bone 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic ultrasound imaging, colour Doppler, and/or MRI can underline the clinical suspicion [3,[7][8][9]. Ultrasound and power Doppler investigations demonstrated unspecific findings like localised swelling, reduced echogenicity, and neovascularisation related to the injured area [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…VISA-A was commonly used in research and was translated to many languages, including Brazilian, Danish, Dutch, French, German, Italian, Spanish, Persian, and Portuguese. 1 , 3 , 7 - 10 , 13 , 14 , 16 However, the original version was developed in English-speaking countries. VISA-A should be translated, adapted, and validated before applying to the Chinese-speaking population.…”
Section: Introductionmentioning
confidence: 99%